Flexible Work Arrangement (FWA) Model for the Commission On Audit Regional Office XII (International Journal of Scientific Research and Management (IJSRM), 2024)
This study described the experiences of the Administration and staff in the implementation of Flexible Work Arrangements (FWA) in the Commission on Audit Regional Office XII (COA XII). Qualitative Case Study Single Approach with embedded unit of analysis was employed, which included interviews of the nine (9) administrators and supervisors as well as the five (5) participants representing the audit clientele of each audit group; and focus group discussion was conducted for the nine (9) staff personnel. For COA XII, guided by its vision, mission and core values and mandate, the overarching consideration is the nationwide policies and legal issuances such as memorandum and circulars. With the interplay of the theoretical frameworks on the Lewis’ theory of change, Ulrich’ HR role model and Fayol’s functions of management, this paper presents the FWA implementation as experienced by the Administrators and staff personnel in every phase of the implementation – (1) Planning Phase: Alignment with Policies/Directives/ Guidelines, Consultative Meetings, and Management by Objectives; (2) Implementation Phase: Structured Workplans/Strategic Task Management, Technological Integration, Clear Communication Protocols, Work-life balance strategies; (3) Feedbacking/ Monitoring Phase: Feedback Collection/Loop, Performance Tracking and Regular Check-ins, Output-focused Monitoring and Accountability; (4) Evaluation Phase: Structured evaluation process, Full digitization of government services, Linking strategic performance management systems with FWA implementation. In managing the audit clientele, the concepts that emerged include (1) open communication for provision of regular updates and value-added insights; and (2) maintaining confidentiality and professionalism thru cooperation and collaboration. There were also facilitating factors and challenges as well as coping mechanisms presented in the paper. All of which were incapsulated as baseline data in proposing the FWA model/framework as guide in ensuring work-life integration and successful implementation of flexible work arrangements in the government sector as well as in the private/non-profit organizations to contribute to the creation of a more flexible and adaptive work environment.